Giant myxofibrosarcoma in the inguinal region with invasion into the same-side scrotum: case report - Xiao, Yufei; Chen, Wei; Fu, Bohua (Frontiers in Oncology, 2025)
BackgroundMyxofibrosarcoma (MFS) is an exceedingly rare malignant neoplasm of fibroblastic origin, characterized by its low clinical incidence. It primarily manifests in the extremities and the posterior trunk, with involvement of the head and neck or abdominal wall being notably uncommon. Epidemiological estimates place their annual incidence at fewer than 0.1 cases per 100,000 population.Case presentationThis case report describes the diagnostic and therapeutic management of an elderly male patient presenting with myxofibrosarcoma located in the right inguinal region, with confirmed pathological invasion into the ipsilateral scrotum. The initial diagnosis was made via ultrasonography and subsequently verified through surgical pathology. The rarity of the tumor’s primary location, coupled with its extensive disease involvement, renders this case the first of its kind documented in the literature.ConclusionIn future clinical practice, a broader spectrum of differential diagnoses should be considered for inguinal-scrotal masses in elderly male patients, including rare entities such as myxofibrosarcoma reported in this study. High-frequency superficial ultrasonography has demonstrated significant clinical value in the preliminary screening of such lesions. The integration of imaging characteristics, clinical presentation, and pathological findings can provide earlier and more accurate guidance for the diagnosis and management of myxofibrosarcoma.